2015
DOI: 10.1002/hrm.21685
|View full text |Cite
|
Sign up to set email alerts
|

“It's All About Time”: Time as Contested Terrain in the Management and Experience of Domiciliary Care Work in England

Abstract: Drawing on a multilevel study of commissioning, employers, and care staff, this article explores the role of time in the management of domiciliary care work for older adults in England and the consequences for the employment conditions of care staff. An index of fragmented time practices among 52 independent-sector domiciliary care providers reveals widespread tendencies to use zero-hours contracts and limit paid hours to face-to-face contact time, leaving travel time and other work-related activities unpaid. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 44 publications
4
115
0
Order By: Relevance
“…Although the research did not focus on electronic monitoring, its final report noted that if electronic monitoring was to become widespread in home care it might reduce pay by ‘restricting paid work time, to time actually spent in people's houses’ (Rubery et al , , p. 4). A more recently published examination of working time based on data from the same study characterized HR practices as relying on the ‘goodwill’ of homecare workers to work more hours than those for which they are paid (Rubery et al ., ; see also Bolton and Wibberley, ).…”
Section: Methodsmentioning
confidence: 92%
“…Although the research did not focus on electronic monitoring, its final report noted that if electronic monitoring was to become widespread in home care it might reduce pay by ‘restricting paid work time, to time actually spent in people's houses’ (Rubery et al , , p. 4). A more recently published examination of working time based on data from the same study characterized HR practices as relying on the ‘goodwill’ of homecare workers to work more hours than those for which they are paid (Rubery et al ., ; see also Bolton and Wibberley, ).…”
Section: Methodsmentioning
confidence: 92%
“…As it has expanded the UK domiciliary sector has therefore seen a relatively small workforce of permanent public sector employees (district nurses and home helps) almost entirely replaced by a much larger number of workers employed by private firms and voluntary sector organizations (who do not have the same social and contractual obligations as public sector organizations). Workers are often on zero‐hours contracts (Rubery et al , ), and many are not paid for the time spent travelling between clients (Wibberley, ). Thus, labour has been externalized to achieve extreme temporal and spatial ‘fragmentation’ (Rubery et al , ; Ungerson, ).…”
Section: Hair and Carementioning
confidence: 99%
“…Workers are often on zero‐hours contracts (Rubery et al , ), and many are not paid for the time spent travelling between clients (Wibberley, ). Thus, labour has been externalized to achieve extreme temporal and spatial ‘fragmentation’ (Rubery et al , ; Ungerson, ).…”
Section: Hair and Carementioning
confidence: 99%
“…In a recent study on nurses led by Halcomb and Ashley (), time constraints were found to be one of the least satisfying aspects of their profession. In the UK, much care work is domiciliary, where care workers are given insufficient time resources to travel and deliver care services (Fleming & Taylor, ; Rubery, Grimshaw, Hebson, & Ugarte, ; Ungerson & Yeandle, ). This time‐related working pressure for caregivers in Europe may be reflected in our data, and while structural issues such as staffing levels may be the main issue, it is nevertheless also identified by caregivers as an aspect of their work which they feel could perhaps be improved by training.…”
Section: Discussionmentioning
confidence: 99%